The Role of Transactional Leadership in Organisational Adaptation to Digitalisation : Systematic Literature Review - Siswadhi, Ferry; Rony, Zahara Tussoleha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Leadership is a key factor in the success of organisations adapting to change, especially those triggered by the development of digital technology so that organisations are required to transform. This research seeks to conduct a literature study of previous studies related to the role of transactional leadership in organisational adaptation to digitalisation. The method used is a systematic literature study including search and processing stages. The search was conducted on several scientific publication databases using several relevant keywords, and found ten articles published in Scopus indexed journals. The results obtained revealed that the majority of studies found a significant role of transactional leadership in organisational adaptation to digitalisation. Some found its contribution to be smaller than other types of leadership. Inherent supervision and rewarding are elements of transactional leadership that encourage organisational adaptation to digitalisation.